The Influence of Marketing Partnership and Sales Promotion on Purchase Intention of Sei Sapi Mancuy Brand on the Grabfood Super App in Bandung City - Saepul Munir, Achmad (Syntax Literate, 2025)
This study explores the effects of Marketing Partnership and Sales Promotion on Purchase Intention of Sei Sapi Mancuy brand through the GrabFood super app in Bandung, Indonesia. A descriptive and verificative research methodology was adopted, involving 100 respondents. Results indicate that both Marketing Partnership and Sales Promotion together positively influence Purchase Intention, but Sales Promotion alone significantly affects Purchase Intention, while Marketing Partnership does not. The findings suggest that enhancing Sales Promotion strategies can increase Purchase Intention among both existing and potential customers